Fight or not fight piracy Is ACTA what we really need? - Regináč, Jozef; Singer, Miroslav, 1968-; Potužák, Pavel; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2012)
Internet piracy has recently been addressed by several policies introduced in US, such as SOPA and ACTA. These policies suggest the general opinion to be that piracy reduce profits. The focus of this thesis is therefore put on the introduction of theoretical concept capable of describing possible piracy impacts and then showing empirical observations to prove it. We developed our own modified time-dependent model of demand function with network effect, which suggests that piracy can have indeed different results on producers' profits depending on the conditions. Further, we showed on real data that the resulting piracy effect in film industry is indefinite and piracy in other industries results in various outcomes.
Vedoucí práce: Miroslav Singer
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses